Peroxiredoxin 2 deletion impairs hippocampal-dependent memory via exacerbating transient ischemia-induced oxidative damage - Jang, Yoon-Sun; Lee, Yo-Seob; Kim, Dong-Hee; Oh, Goo Taeg; Jeon, Won Kyung; Han, Jung-Soo (Elsevier BV, 2022)
Peroxiredoxin 2 (Prx2) regulates oxidative stress response in neuronal injury. The present study examined the effects of Prx2 deletion on transient global ischemia-induced hippocampal-dependent memory impairment. First, 20-min bilateral common carotid artery occlusion (BCCAO)-reperfusion and sham-operated control procedures were conducted in 6-or 7-month-old Prx2 knockout and wild-type mice. The cognitive status of these mice was assessed using the Morris water maze task with a hidden platform and a novel object recognition task 7 days after the 20-min BCCAO. Next, to evaluate neuronal degeneration and oxidative stress in the CA1 subregion of the hippocampus critical for learning and memory, we measured immunoreactive Fluoro-jade C (FJC)-positive signals and 4-hydroxy-2-trans-nonenal (4-HNE) levels, respectively. The 20-min BCCAO induced cognitive impairments and increased the intensity of FJC-positive signals and 4-HNE levels of CA1 in Prx2 knockout mice but not in wild-type mice. These results suggest that Prx2 deficiency reduces resilience to transient global ischemia.